Cooled Multifunctional Platforms to Alleviate Heat Stress in Broiler Chickens: Effects on Performance, Carcass and Meat Quality Traits - Bassem Khalfi; Kobe Buyse; Imad Khan; Camila Lopes Carvalho; Patricia Soster; Gunther Antonissen; Frank André Maurice Tuyttens (Animals)
Platforms have been shown to be a suitable environmental enrichment for broiler chickens, accommodating their motivation to roost and rest at an elevated position. In order to increase the animal welfare benefits, we designed prototype elevated platforms with additional functionalities: a local cooling system, a sheltered area underneath the platform and collection trays underneath the platform that prevent manure from falling on the litter. This study assessed the effects of these multifunctional platforms during thermoneutral and heat stress conditions on two key determinants of their commercial uptake potential, namely production performance, carcass and meat quality. In each of the three experimental rounds, 560 one-day-old male chicks (Ross 308) were equally assigned to four pens and reared for 43 days. The barn was divided into two compartments (thermoneutral and heat), each containing one enriched and one barren pen. To induce heat stress, the ambient temperature was increased to 32 °C during 6 h/day when the birds were 29–40 d old. The platforms did not compromise broiler performance. Heat stress negatively impacted body weight (p = 0.008), average daily gain (p = 0.009) and feed intake (p < 0.001) and improved the feed conversion ratio (p = 0.026). The platforms reduced mortality rate under heat stress but not under thermoneutral conditions (heat × enrichment p = 0.025), likely due to the cooling functionality. No major effects of the platforms on overall carcass and meat quality were observed, except for a reduction in the risk of breast muscle myopathies (p < 0.001), which could enhance consumer acceptance and improve profitability. To conclude, the use of cooled platforms under the conditions of this experiment mitigated the adverse effects of heat stress on mortality, reduced the risk of breast muscle myopathies and did not compromise any other production or carcass and meat quality parameters.